2020
DOI: 10.48193/rmu.v80i2.619
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and extended spectrum beta-lactamases in urinary tract infections: A serious problem in Northern Mexico

Abstract: Objective: To describe the causal agents, prevalence of antimicrobial resistance, and risk factors associated with extended spectrum beta-lactamase (ESBL)-producing agents in urinary tract infections (UTIs). Materials and methods: A retrospective study was conducted at a tertiary care hospital in Monterrey, Mexico. Inclusion criteria were patients that clinically presented with a UTI and had a positive urine culture, within the time frame of March to October 2017. The association with ESBL-producing agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, they suggested that the use of gentamicin and fluoroquinolones should be avoided due to the high rates of resistance reported in this population [ 14 ]. The previous recommendations do not seem to be adequate for our population, since it was demonstrated in a previous study that the resistance rate to third generation cephalosporins was higher (48%) [ 9 ], and increased to 52.1% in patients with EPN. In our population, empirical use of carbapenems seems to be the treatment of choice, adjusting the treatment according to the resistance profile as soon as the sensitivity patterns are available.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, they suggested that the use of gentamicin and fluoroquinolones should be avoided due to the high rates of resistance reported in this population [ 14 ]. The previous recommendations do not seem to be adequate for our population, since it was demonstrated in a previous study that the resistance rate to third generation cephalosporins was higher (48%) [ 9 ], and increased to 52.1% in patients with EPN. In our population, empirical use of carbapenems seems to be the treatment of choice, adjusting the treatment according to the resistance profile as soon as the sensitivity patterns are available.…”
Section: Discussionmentioning
confidence: 83%
“…In a previous study carried out in our center, it was determined that the rate of ESBL-producing microorganisms in non-gas-forming urinary tract infections was 21.5%, compared to 31.7% reported in EPN in the present study. Third generation cephalosporins, fluoroquinolones [ 8 ], and carbapenemics were reported with higher resistance rates between patients with EPN compared to non-gas-forming infections [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies in Mexico have assessed the fosfomycin resistance rates among uropathogenic E. coli strains [ 15 , 16 ]; however, none reported the molecular mechanism of resistance against this agent. Furthermore, information on the incidence of plasmid-mediated fosfomycin resistance in ESBL-producing E. coli strains isolated from urine is lacking in our country.…”
Section: Introductionmentioning
confidence: 99%